FAKTOR–FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU BULLYING PADA REMAJA - Hertika Nanda Putri; Fathra Annis Nauli; Riri ' Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract   Bullying phenomenon in schools is a worldwide problem that can have negative lifelong consequences for students. This research aims to identify the correlation between the internal and external factors related to bullying behaviour on adolescents. The research used correlation method with cross sectional approach. Chi Square test used to analyze the data on 83 students class of 10th and 11t in SMA Negeri 7 Pekanbaru. Sample was taken by using simple random sampling. Results showed that there was a correlation between genders, personality type, self confidence, school climate and peer social group on adolescents. The statistic showed that genders (p=0.003< alpha=0.05), personality type (p=0.021< alpha=0.05), self confidence (p=0.033< alpha=0.05), school climate (p=0.032< alpha=0.05), and peer social support (p=0.000< alpha=0.05) which means that there was a correlation between variables with bullying behaviour among adolescents. This study suggested any stakeholders particularly teacher to increase bullying prevention activities, further identify the factors that led to the appereance of bullying behaviour on adolecents in high school. Keywords : Adolescents, bullying, external factor, internal factor